2011
DOI: 10.1111/j.2040-1124.2011.00156.x
|View full text |Cite
|
Sign up to set email alerts
|

Obesity may attenuate the HbA1c‐lowering effect of sitagliptin in Japanese type 2 diabetic patients

Abstract: Aims/Introduction:  The aim of the present study was to assess the independent predictors of the HbA1c‐lowering effect of sitagliptin in Japanese type 2 diabetic patients.Materials and Methods:  Data were retrieved from the medical records of 151 type 2 diabetic patients who had been taking sitagliptin 25 or 50 mg once daily for inadequate glycemic control for at least 12 weeks, with or without other oral hypoglycemic agents. Spearman’s rank correlation coefficients were calculated to investigate correlations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 26 publications
(34 reference statements)
4
22
1
Order By: Relevance
“…We recently reported that another GLP-1 analogue, liraglutide, is more effective in earlier stages of diabetes (30). Similarly, sitagliptin, the first oral DPP-4 inhibitor, is more effective in patients with a shorter duration of diabetes (31). Likewise, in patients whose glycemic control is worsened by GC therapy, it is plausible to consider that earlier intervention with exenatide is more effective as well as other incretin-related drugs.…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that another GLP-1 analogue, liraglutide, is more effective in earlier stages of diabetes (30). Similarly, sitagliptin, the first oral DPP-4 inhibitor, is more effective in patients with a shorter duration of diabetes (31). Likewise, in patients whose glycemic control is worsened by GC therapy, it is plausible to consider that earlier intervention with exenatide is more effective as well as other incretin-related drugs.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that loss of the incretin effects was more extensive in obese than in lean type 2 diabetic patients [25]. More recently, Bando et al reported that obesity may attenuate the HbA 1c -lowering effect of sitagliptin in Japanese type 2 diabetic patients [26]. This suggests that lipids may be involved in the regulation of incretin responsiveness in pancreatic beta cells.…”
Section: Introductionmentioning
confidence: 99%
“…In previous reports involving larger cohorts than the present study, or in which most of the participants had BMI values of 22 to <30 kg/m 2 , the baseline BMI was related to the HbA1c-lowering effect of sitagliptin (8-10). Thus, in the present study the power of detection might have been somewhat weak.…”
Section: Discussionmentioning
confidence: 45%
“…However, some Japanese retrospective studies have shown a negative correlation between the glucose-lowering efficacy of sitagliptin (a DPP-4 inhibitor) and the baseline body mass index (BMI) value (8-10). On the other hand, other studies found no relationship between the glucose-lowering efficacy of DPP-4 inhibitors and the BMI (11,12).…”
Section: Introductionmentioning
confidence: 99%